HPLC On-line ABTS+ Antioxidant screening 시스템을 이용한 한국산 녹차로부터 Catechin compounds의 황산화 활성분석 - 이광진 (한국생물공학회, 2008)
In this work, we describes analysis of the antioxidant potential of Korean green tea phenolics using an high-performance liquid chromatography (HPLC) on-line ABTS+ antioxidant screening method. In conjunction with the analysis of their 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS+) radical scavenging ability, the extraction of catechine compounds from Korean green tea were performed by various temperature and time. The optimum operating conditions were experimentally determined to analyze the catechine compounds in the pretreatment extracts. From the results, the extraction temperature 60℃, time 3 min was selected as an optimal antioxidant activity condition. The analysis by C18 column was performed, the flow rate of mobile phase and UV wavelength was fixed at 1.0 ml/min and 254 nm, respectively. the mobile phase was composed from acetonitrile and water, and the gradient elution mode were applied.